Extração e obtenção de encapsulado de taturubá (Pouteria macrophylla (Lam) Eyma.) rico em substâncias bioativas - Leal, Gabriela Fonseca (Universidade Federal do Tocantins, 2024)
Originating from the legal Amazon, taturubá (Pouteria macrophylla (Lam) Eyma.) is a fruit recognized for being a natural source of phenolic compounds identified by their potential to reduce oxidative stress in the body's cells. However, little is known about its nutritional characteristics and optimization of the extraction process of its bioactive compounds. Therefore, the objective of this study is to evaluate the combination of different extraction methods and deep eutectic solvents for the quantification of bioactive substances from taturubá, as well as the encapsulation of these compounds using extrusion and ionic gelation. For this, the nutritional composition and quantitative analyzes of the portions of the fruit were investigated. In the extraction of bioactive compounds, a 4x2 factorial was applied, using three deep eutectic solvents (choline chloride + acetic acid, choline chloride + lactic acid and menthol + lactic acid) and a control solvent (80% ethanol), combined with two extraction methods (maceration and ultrasound bath). The best extract from each portion was encapsulated using the combined extrusion and ionic gelation method. The results demonstrated that the peel and pulp fraction have a high carbohydrate content, especially sucrose and fructose and a source of minerals, especially iron, while the seed demonstrated to be rich in protein, with the presence of the essential amino acids leucine, lysine and valine. The peel, pulp and seed fractions showed a high content of gallic acid, syringic acid and trigonelline. The solvents choline chloride + acetic acid and 80% ethanol showed the best extraction results for bioactive and antioxidant substances and the ultrasound bath extraction method was the most significant in the analyses. Among the bioactive compounds, total phenolics and flavonoids were most prominent. The encapsulation method combining extrusion and ionic gelation showed effectiveness in the formation of uniform and homogeneous microcapsules, however it presented low encapsulation efficiency. During storage, microcapsules exposed to light exhibited a greater reduction in encapsulated phenolic compounds during the days compared to microcapsules stored in the absence of light. In this way, the taturubá fruit has great attraction for extracting bioactive compounds in all its portions, making its application in the food, pharmaceutical and cosmetic industries possible.